The 3D stereotaxic brain atlas of the degu : with MRI and histology digital model with a freely rotatable viewer /: with MRI and histology digital model with a freely rotatable viewer. (2018) - Kumazawa-Manita, Noriko; Hashikawa, Tsutomu; Iriki, Atsushi
No abstract available